FUNGSI KOORDINASI DALAM MENUNJANG PELAKSANAAN TUGAS APARATUR SATUAN POLISI PAMONG PRAJA DAN PEMADAM KEBAKARAN KABUPATEN SIGI - Sipanawa, Ruliyanto E.; Riadi, Slamet; Mustari, Hasanuddin (Katalogis, 2019)
Civil Servants Police Unit and Sigi District Fire Department. This research uses descriptive qualitative type, with the number of informants involved as many as 6 informants through purposive sampling technique. In addition, in data collection techniques in this study through observation, interviews, documentation and study of literature. With the method of data analysis with three steps, namely (1) data reduction, (2) data display, and (3) conclusions or verification. From the results of the research researchers note that the implementation of the coordination function of the Civil Service Police Unit and the Sigi District Fire Department still has not been implemented optimally, this is because the coordination of integration aspects is still not going well, this is caused by there are still some officials who do not obey some of the results coordination as agreed upon. Besides that, the communication aspect is still not running well, this is because sometimes there are still miscommunications between apparatus which are divided into several work units in the agency in carrying out their duties. In addition, vertical communication is still not running well, where reciprocal communication between leaders and subordinates is still running poorly, employees sometimes do not coordinate first with their superiors when facing problems on the ground, they take their own actions which ultimately fatal impact on the achievement of the agency in carrying out its work activities.